STUDY OF WOMEN ROLE IN INDIA UNDER MANU LAW (Journal of history-rus, 2022)
During the ancient time in India, there was no comprehensive book about law, only (DharmaShastra) by Brahmans which used the households and the lives of the people that were the most ancient law which can introduce the task of every cast, the Dharma-Shysters, consisting about all of 2685 poems that the History of that concern to 1200 B.C. This law at the first was only for Brahmas at least slowly accepted by every one of Hindu people. An ethical code with the cast system is a necessary and necessity rule. If the cast disciple was collapsed the ethical discipline also had fallen from the role. This law has two points: first of that was the commemoration of the Bahrainis, the second was respectable of the cow, and also the childbearing was another side of this law. In Manu’s law, the perfect family should stand by three-pillar, Husband, wife, and son. According to education and wealth, according to the sati tradition, women who adopted this rule, Indians paid attention to their correctness and dialogue, according to Huang Zhuang’s theory, Indian women are responsible for their cleanliness, carelessness in dress, attention to embellishment of appearance. The best view of people and the game of chess comes through religious holidays. Key words: Dubois, Sati, Brahmin, Gateau, Durga, Arthasastra.